SAT0448 BONE HEALTH IN PATIENTS WITH PSORIASIS ARTHRITIS IN THE SWISS NATIONAL COHORT: A CROSS-SECTIONAL STUDY. (2nd June 2020) - Youssef, I.; Aubry-Rozier, B.; Aeberli, D.; Dan, D.
Abstract : Background: There is much controversy surrounding the loss of bone mass in patients with psoriasis arthritis (PsA). Objectives: To evaluate the prevalence of osteoporosis (OP) and fracture in patients with PsA in the Swiss Clinical Quality Management (SCQM) cohort, a large national database of patients with inflammatory arthritis; to study different factors influencing bone health and the correlation between disease activity, treatment and occurrence of densitometric osteoporosis or fracture. Methods: We analyzed all PsA-patients included in the cohort from 2006-April 2019. We evaluated demographic and clinical data: age, gender, BMI, disease duration, smoking/alcohol habits, patient's and physician's global assessment, joint count, HAQ, medication and inflammatory activity measured by ESR, CRP, DAS 28 and DAPSA score. We compared patients with BMD measurement (DXA) with the group without DXA (nDXA). In DXA group we analyzed patients according to osteoporotic status and did subgroup analysis in premenopausal, menopausal women and men. Results: Of the 2443 patients, 545 had a DXA. Age of scanned patients was 18-84 years. Only 295 BMD data were available for analysis. DXA patients were 6.4 years older (54.2±11, 1 vs 47.8±12.4 years, p<0.001), and were more female (67% vs 43%). Duration of the disease was longer (6.6±8.3 vs 5.3±7.1 y, p<0.001) in DXA group. DAS28-CRP and DAS28-ESR were higher in DXA group (3, 1 ± 1, 2 vs 2, 9 ± 1, 1, p< 0, 04 and 3, 2 ± 1, 4 vs 3 ± 1, 3, p< 0, 002, respectively), as was the DAPSA score (32 ± 30 vs 27 ± 20 p<0.04). Patients in DXA group were more exposed to prednisone and conventional DMARDs (15.4% vs 4.7%, p<0.001 and 51.7% vs 43%, p<0.01 respectively). There were more fractures in DXA- than in nDXA group (5.7% vs 1.4%, P< 0.001). In DXA group 18.4% patients had OP and 50.2% osteopenia. Patient characteristics are shown in Table 1 . We confirmed a positive correlation between femoral and lumbar BMD and BMI, and between higher age and lower femoral BMD. Disease duration was inversely correlated with femoral, but not lumbar BMD. Interestingly, other variables, including disease activity, showed no significant correlation with the BMD, but OP patients had higher disease activity. Subgroup analysis (Figure 1 ) showed higher OP prevalence in postmenopausal women (22, 6%) vs in men (16.8%) or premenopausal women (10.7%) in concordance with the fracture rate (8.3% vs 6.3% vs 3.9%). BMD was lower and the disease activity was higher in postmenopausal women compared to the others groups. Conclusion: Our data suggest that Swiss clinician are aware of risk of poor bone-health in PsA patients and perform DXA in this population even in younger patients and in men. Interestingly, we describe that the patients with OP had higher disease activity and poorer functional status than patients without OP. Longitudinal studies are needed to evaluate bone quality, fractures, and relationship between bone health in PsA and disease associated factors. They should integrate parameters of bone turnover and use an appropriate control group. Disclosure of Interests: None declared